"When Nothing Matters, Things Just Happen": Young Parenting Women's Reflections on Caring, Health, and Justice. (April 2014) - Gubrium, Aline; Barcelos, Christie; Buchanan, David; Gubrium, Erika
The field of public health frequently issues calls for social justice, but it is not clear that everyone agrees on what this means or how to achieve it. To assess lay citizens' views on the relationship between justice and health, we conducted individual interviews with 19 young parenting women to hear and discuss their thoughts about the causes of health disparities, ways to reduce them, and the nature of the just society. A salient theme to emerge in these interviews was the topic of "caring." This article reports on four categories identified under the theme of caring: 1) observations of apathy and indifference; 2) the effects of not caring; 3) models of caring; and 4) the pull of caring. Based on these results, the article outlines a grounded theory on the role of caring in conceptualizing health motivation.